Exclusion and Discrimination in Access to Education Against Afghanistan Women: An International Human Rights Study - Marsanthy, Talitha Aqiella (LifeSciFi, 2025)
The Taliban’s return as the de facto authority in Afghanistan in 2021 has led to severe restrictions on Afghan women’s right to education, particularly through the closure of secondary and higher education institutions for female students. These policies raise significant concerns about violations of international human rights standards set out in the ICESCR, CEDAW, and the CRC, as well as their related General Comments and General Recommendations. This study aims to analyze how these restrictions constitute violations of women’s right to education under international human rights law and to examine the state’s responsibility for such violations. Using a normative juridical method with statute and comparative approaches, the research finds that the Taliban’s actions represent discriminatory acts of commission that contradict core human rights principles, especially equality and non-discrimination. The study also shows that Afghanistan remains legally bound by its treaty obligations despite changes in governance. Therefore, strengthening international accountability mechanisms such as UN treaty bodies, particularly the CEDAW Committee, is essential to ensure acknowledgement of violations, provision of reparations, and guarantees of non-repetition. The study concludes that systemic exclusion of women from education constitutes a clear breach requiring urgent international oversight.